Fluorescent glycoprobes: a sweet addition for improved sensing. Issue 1 (14th October 2016) - He, Xiao-Peng; Zang, Yi; James, Tony D.; Li, Jia; Chen, Guo-Rong; Xie, Juan
Abstract : We highlight recent progress from our labs for the development of fluorescent glycoprobes for sensing ions/lectins and targeted detection of intracellular species, including the construction of their 2D material composites for targeted fluorescence imaging and theranostics. Abstract : The development of small-molecule fluorescent probes for the detection of ions and biomacromolecules and for cellular and in vivo imaging has been a very active research area. Nevertheless, many problems exist for traditional probes including their poor water solubility, toxicity and the inability to target specific tissues. Because of the enhanced water solubility, biocompatibility and targeting ability for specific cells, there has been an emerging movement to use carbohydrates as either the backbone or as a warhead to decorate conventional fluorescent probes, producing "glycoprobes" with enhanced properties. This feature article provides an overview of recently developed glycoprobes for ion and protein detection as well as targeted (receptor targeting) cellular imaging and theranostics. Here, we summarise the tactics for preparing small molecular glycoprobes and their supramolecular 2D material composites.